2014
DOI: 10.1016/j.ridd.2014.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Can children with autism read emotions from the eyes? The Eyes Test revisited

Abstract: This study aimed to test two new, simplified tasks related to the eye-test, targeting children with Autism Spectrum Disorder (ASD) and typically developing controls (TD). Test-1 assessed the recognition of emotion/mental states with displays using one word and two eyepictures, whereas Test-2 presented displays using two words and one eye-picture. Black and white photographs of children were used as materials. A cross-cultural study (Caucasian/East-Asian) with adults was initially carried out to verify generali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 60 publications
1
27
0
1
Order By: Relevance
“…Happiness, disgust, and neutral are all mostly recognized from the mouth region (29)(30)(31), and thus it may be that children with ASD are not used to recognizing these emotions from the eye area. Our findings support those of Fink et al (15) and Nuske et al (16), as eye region ER deficits in ASD appear not to be systematic or universal: Berggren et al (17) found deficits in happiness recognition in Scandinavian children with ASD, Franco et al (3) found deficits in happy/surprise and sad/angry definition in multi-ethnic, English children with ASD, and Kuusikko et al (18) found deficits in general ER in Scandinavian children with ASD.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Happiness, disgust, and neutral are all mostly recognized from the mouth region (29)(30)(31), and thus it may be that children with ASD are not used to recognizing these emotions from the eye area. Our findings support those of Fink et al (15) and Nuske et al (16), as eye region ER deficits in ASD appear not to be systematic or universal: Berggren et al (17) found deficits in happiness recognition in Scandinavian children with ASD, Franco et al (3) found deficits in happy/surprise and sad/angry definition in multi-ethnic, English children with ASD, and Kuusikko et al (18) found deficits in general ER in Scandinavian children with ASD.…”
Section: Discussionsupporting
confidence: 90%
“…Previous meta-analyses of ER show that ER is more accurate within the same cultural group, compared to cross-cultural ER (1,2). However, this in-group advantage appears to diminish in typically developing (TD) populations, when ER is made to rely primarily on the eye region (3,4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Less is known about the association of EF to emotion recognition abilities that are theoretically considered to be equally fundamental aspects of ToM and empathising in general (Golan et al, 2006). Indeed recent evidence has suggested that ToM should not be considered a single process as it includes two levels: cognitive and affective (Baron-Cohen et al 2015;Franco et al, 2014;Mazza et al, 2014Mazza et al, , 2017Shamay-Tsoory et al, 2009). Cognitive ToM refers to the ability to understand one's mental states (e.g.…”
Section: Ef and Tom In Asdmentioning
confidence: 99%
“…Específicamente, el componente cognitivo es la capacidad de entender lo que otros están pensando (es decir, sus estados mentales). Mientras que el componente afectivo es la capacidad de hacer inferencias con respecto a las emociones de otras personas (Franco et al, 2014;Mazza et al, 2014;Pino et al, 2016;Shamay-Tsoory, Tomer & Aharon-Peretz, 2005).…”
Section: Desarrollo De La Teoría De La Mente En Niños Con Teaunclassified